Adsorption method, composition with swelling polymer and use thereof

By mixed solvents induced polymer swelling and modification, the problem of unsatisfactory adsorption performance of the existing polymer has been solved, and the effect of improving adsorption and firmness is achieved, which is suitable for a variety of application scenarios.

CN115501647BActive Publication Date: 2025-01-28TIANJIN POLYTECHNIC UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110631980.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-06-07
Publication Date
2025-01-28
Estimated Expiration
2041-06-07

AI Technical Summary

Technical Problem

Due to its chemical structure, the adsorption performance of existing polymers is not ideal, and there are problems such as small adsorption amount and easy adsorption quality to fall off.

Method used

By using hybrid solvents to induce polymer swelling and modification, select the well -known solvents and adverse solvents of the polymer matrix into a hybrid solvent, and place the polymer matrix and adsorption in a mixed solvent to make it adsorbed Devil and bloating treatment restores the original state.

Benefits of technology

Under the premise of not destroying the polymer matrix, it improves its adsorption of small molecules or macromolecules and adsorption firmness. The operation is simple. The bloating solution is easy to recycle and is universal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115501647B_ABST
    Figure CN115501647B_ABST
Patent Text Reader

Abstract

This invention provides an adsorption method, a composition having a swollen polymer, and its application. The adsorption method includes the following steps: step a) preparing a good solvent and a poor solvent for the polymer matrix to form a mixed solvent; step b) placing the polymer matrix and the adsorbate in the mixed solvent formed in step a), causing the polymer matrix to adsorb the adsorbate in a swollen state. The adsorption method provided by this invention utilizes mixed solvent-induced swelling modification, which can improve the adsorption capacity and adsorption strength of small or large molecules without damaging the polymer matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of adsorption and impurity removal, adsorption modification, dyeing and pharmaceutical preparation, and in particular to an adsorption method, a composition with a swelling polymer and application thereof. Background Art

[0002] The adsorption properties of polymers are widely used in many fields. Some polymers can adsorb small molecules. In the field of water treatment, they can remove pollutants in domestic sewage and industrial wastewater, such as dyes, heavy metal ions and gasoline. In the field of medicine and health, they can adsorb drugs and serve as carriers for delivery and release. They can adsorb bilirubin in red blood cells and remove toxic components accumulated in the blood of patients with renal failure. In the field of printing and dyeing, they can adsorb various required dye small molecules to obtain textiles with various colors. In addition, polymers can adsorb large molecules to improve their surface hydrophilicity, antibacterial properties and biocompatibility or prepare composite membranes.

[0003] Due to their chemical structure, some polymers have unsatisfactory adsorption performance, resulting in problems such as low adsorption capacity and easy detachment of adsorbate. Summary of the invention

[0004] In view of the above-mentioned defects in the prior art, the present invention provides an adsorption method, a composition having a swelling polymer and its application. The present invention utilizes a mixed solvent to induce swelling modification, which can increase the adsorption amount and adsorption firmness of small molecules or macromolecules without destroying the polymer matrix.

[0005] According to a first aspect of the present invention, there is provided an adsorption method, comprising the following steps:

[0006] Step a) selecting a good solvent for the polymer matrix and a poor solvent for the polymer matrix according to the polymer matrix used and preparing a mixed solvent;

[0007] Step b) placing the polymer matrix and the adsorbate in the mixed solvent formed in step a) so that the polymer matrix adsorbs the adsorbate in a swollen state.

[0008] According to some embodiments of the present invention, in step a), the mass ratio of the good solvent to the poor solvent is 1:9 to 4:1.

[0009] According to some embodiments of the present invention, the good solvent and the poor solvent are relative to the polymer matrix used. A specific solvent is a good solvent for a certain polymer matrix, but may be a poor solvent for another polymer matrix.

[0010] In the present invention, the good solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, n-hexane, water, dichloromethane, n-butanol, dioxane and tetrahydrofuran, preferably N,N-dimethylformamide.

[0011] The poor solvent includes one or more of ethanol, methanol, propanol, acetone, chloroform, ethyl acetate, hexane, toluene, ether and water, preferably water.

[0012] According to some embodiments of the present invention, the polymer matrix in step b) comprises one or more of rubber, plastic and fiber.

[0013] In some specific embodiments, the polymer matrix in step b) is polyacrylonitrile and / or polyvinylidene fluoride; and in some specific embodiments, the good solvent is N,N-dimethylformamide, and the poor solvent is water.

[0014] The polymer matrix is ​​in the form of one or more of a film, a fiber, a gel, a microsphere, a fabric and a microcapsule, preferably in the form of a film.

[0015] The mass fraction of the polymer matrix relative to the mixed solvent in step a) is 0.1-2%, preferably 0.5-1.5%, and more preferably 0.8-1.2%.

[0016] According to some embodiments of the present invention, the swelling of the polymer matrix in step b) is carried out at a temperature ranging from 25°C to the glass transition temperature of the polymer matrix, preferably 30-80°C, more preferably 40-60°C.

[0017] According to some embodiments of the present invention, the adsorbate in step b) includes macromolecular substances and / or small molecular substances.

[0018] The macromolecular substance includes one or more of a hydrophilic polymer, a hydrophobic polymer and an amphiphilic polymer. The hydrophilic polymer is preferably one or more of polyvinyl alcohol, chitosan, polydimethylaminoethyl methacrylate, and heparin, the hydrophobic polymer is preferably polydimethylsiloxane or protein, and the amphiphilic polymer is preferably one or more of polymethacrylate betaine, polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer and polymethacrylate glycol ester, more preferably polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer.

[0019] The small molecule substance includes one or more of inorganic small molecules, metal ions and organic small molecules, and is preferably methylene blue.

[0020] According to some embodiments of the present invention, the adsorption method further comprises:

[0021] Step c) immersing the polymer matrix adsorbed with the adsorbate in step b) in a poor solvent for deswelling treatment.

[0022] In step c), the swollen and adsorbed polymer matrix is ​​immersed in a poor solvent for deswelling treatment, and the good solvent in the polymer matrix diffuses into the poor solvent, thereby removing the good solvent in the polymer matrix to restore the polymer matrix to its original state (i.e., non-swollen state).

[0023] In some specific embodiments, the deswelling treatment comprises drying the polymer matrix containing the adsorbate, the drying temperature is room temperature to 50° C., and the drying time is 5 to 30 minutes.

[0024] According to a second aspect of the present invention, a composition having a swollen polymer is also provided, comprising: a polymer matrix; a mixed solvent comprising a good solvent for the polymer matrix and a poor solvent for the polymer matrix. The composition of the present invention can be used in the adsorption method as described above.

[0025] According to some embodiments of the present invention, the polymer matrix includes one or more of rubber, plastic and fiber, preferably polyacrylonitrile or polyvinylidene fluoride.

[0026] In the present invention, the polymer matrix may be in the form of one or more of a film, a fiber, a gel, a microsphere, a fabric and a microcapsule, preferably in the form of a film.

[0027] According to some embodiments of the present invention, the mass fraction of the polymer matrix relative to the mixed solvent in step a) is 0.1-2%, preferably 0.5-1.5%, and more preferably 0.8-1.2%.

[0028] According to some embodiments of the present invention, the mass ratio of the good solvent to the poor solvent is 1:9 to 4:1.

[0029] The good solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, n-hexane, water, dichloromethane, n-butanol, dioxane and tetrahydrofuran. For example, in some embodiments, N,N-dimethylformamide can be used as the good solvent.

[0030] The poor solvent includes one or more of ethanol, methanol, propanol, acetone, chloroform, ethyl acetate, hexane, toluene, ether and water. For example, in some embodiments, water can be used as the poor solvent.

[0031] In some specific embodiments, the polymer matrix is ​​polyacrylonitrile and / or polyvinylidene fluoride; and in some specific embodiments, the good solvent is N,N-dimethylformamide, and the poor solvent is water.

[0032] According to the third aspect of the present invention, there is also provided an adsorption method as described in the first aspect or a use of the composition having a swelling polymer as described in the second aspect in biology, water treatment, printing and dyeing, and surface modification.

[0033] The beneficial aspects of the present invention are:

[0034] (1) The adsorption method provided by the present invention is used to make the polymer swell in a mixture of its own good solvent and poor solvent. This method of using a mixed solvent to induce swelling modification can increase the adsorption amount and adsorption firmness of small molecules or macromolecules without destroying the polymer matrix. According to an exemplary embodiment, the macromolecules adsorbed by the polymer in the swollen state are firmly planted on the polymer surface.

[0035] Specifically, the swelling degree of the polymer matrix can be controlled by controlling the concentration of the good solvent, and mixing with the poor solvent can avoid damage to the polymer matrix caused by excessive swelling degree of a single solvent or insufficient solvation to achieve the desired swelling effect.

[0036] (2) The adsorption method of the present invention is a method utilizing swelling modification, which is simpler to operate than other adsorption modification methods. The swelling liquid used is also easy to be recycled. Most of the polymers used for adsorption have their own good solvents and poor solvents, so the swelling modification method provided by the present invention has universal applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 FIG. 1 is a flow chart of an adsorption method according to an exemplary embodiment of the present invention.

[0038] Figure 2 The present invention is a flow chart of an adsorption method according to another exemplary embodiment of the present invention.

[0039] Figure 3 The SEM images of the PAN film treated with different good solvent concentrations and different temperatures according to Example 1 of the present invention are shown.

[0040] Figure 4 These are XRD diagrams of the PAN membrane of Example 1 of the present invention, the PAN membrane after swelling, and the PAN membrane after deswelling.

[0041] Figure 5 This is a FIB-SEM image of the PVDF membrane treated with different good solvent concentrations and different temperatures according to Example 2 of the present invention.

[0042] Figure 6These are XRD diagrams of the PVDF membrane of Example 2 of the present invention, the PVDF membrane after swelling, and the PVDF membrane after deswelling.

[0043] Figure 7 This is an electron microscope image of platelets adsorbed on the surface of a PVDF membrane in Example Y of the present invention.

[0044] Figure 8 This is an electron microscope image of red blood cells adsorbed on the surface of the PVDF membrane in Example Y of the present invention. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] According to the above-mentioned background technology, some polymers cause adsorption performance to be undesirable due to their chemical structure, and there are problems such as less adsorption amount and easy fall-off of adsorbate. For example, polyacrylonitrile is widely used in many fields such as clothing textiles, water treatment, etc. due to its good chemical stability, flame retardancy and anti-oxidation degradation, but the stereoregularity of polyacrylonitrile is high, and the interaction force between macromolecules and their aggregates is strong, which is shown as the molecular structure of polyacrylonitrile is tight and stable, so adsorption performance is extremely bad. Polymers such as polyvinylidene fluoride and polysulfone have excellent mechanical properties, heat resistance, chemical corrosion resistance and film-forming properties, are widely used in separation and purification fields, and are nontoxic in addition, and have also been widely used in the field of biomaterials. However, these materials themselves have very strong hydrophobicity, are easy to be polluted in use, and often need to improve surface properties by adsorbing hydrophilic macromolecules on their surface for this reason, but the interaction force between the adsorbed molecules and the substrate surface is not strong usually, and there is poor adsorption stability, and the problem that adsorbate easily falls off.

[0047] At present, in order to solve the above problems, the methods for improving the adsorption performance of polymers include: (1) chemical modification of the polymer matrix, which is mainly obtained by grafting or hydrolysis. However, the grafting process involved in grafting modification is generally very complicated and not suitable for large-scale operation. The residual acid and alkali in the hydrolysis modification method will have a certain destructive effect on the surface of the material and cause pollution to the environment, and cannot be directly discharged; (2) physical modification of the polymer matrix, mainly including blending the polymer matrix with other substances, surface coating and other methods to obtain the desired performance. Blending modification has changed some of the excellent properties of the polymer itself, and the additives are easily released from the blended material. During the application process of the coating method, the surface coating may fall off the polymer surface, and the modification effect is not long-lasting and stable. For example, Shi et al. [1] used blending modification to prepare hydrophilic membranes. The additives used were easily released from the blended material, reducing the modification effect and causing secondary pollution. In addition, Sundaram et al. [2] coated dopamine on the polymer surface to increase the polymer adsorption effect. The coating method modified the polymer adsorption properties through physical action. Over time, the coating easily fell off the polymer surface, and the modification effect was not long-lasting and stable.

[0048] In view of this, the present invention provides an adsorption method, which utilizes a mixed solvent to induce polymer swelling modification, thereby increasing the adsorption amount and adsorption firmness of small molecules or macromolecules without destroying the polymer matrix.

[0049] Figure 1 FIG. 1 is a flow chart of an adsorption method according to an exemplary embodiment of the present invention.

[0050] See also Figure 1 According to an exemplary embodiment, in step S101, a good solvent for the polymer matrix and a poor solvent for the polymer matrix are selected according to the polymer matrix used to prepare a mixed solvent. Then, the process proceeds to S102.

[0051] In step S102, according to some embodiments, the polymer matrix and the adsorbate are placed in the mixed solvent formed in step S101, so that the polymer matrix is ​​in a swollen state to adsorb the adsorbate.

[0052] According to an exemplary embodiment, the present invention utilizes a mixed solvent to induce swelling of a polymer matrix, which can increase the amount of adsorption and the firmness of adsorption of small molecules or macromolecules without destroying the polymer matrix.

[0053] Figure 2 The present invention is a flow chart of an adsorption method according to another exemplary embodiment of the present invention.

[0054] See also Figure 2According to an exemplary embodiment, in step S201, a good solvent for the polymer matrix and a poor solvent for the polymer matrix are selected according to the polymer matrix used to prepare a mixed solvent.

[0055] According to some embodiments, the mass ratio of the good solvent to the poor solvent of the selected polymer matrix is ​​1:9 to 4:1.

[0056] According to an exemplary embodiment, the good solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, n-hexane, water, dichloromethane, n-butanol, dioxane and tetrahydrofuran. In some embodiments, the good solvent can be selected from N,N-dimethylformamide.

[0057] According to an exemplary embodiment, the poor solvent includes one or more of ethanol, methanol, propanol, acetone, chloroform, ethyl acetate, hexane, toluene, ether and water. In some embodiments, the poor solvent can be water. Then, the process proceeds to S202.

[0058] In step S202, the polymer matrix and the adsorbate are placed in the mixed solvent formed in step S201, so that the polymer matrix is ​​in a swollen state to adsorb the adsorbate.

[0059] According to an exemplary embodiment of the present invention, the polymer matrix in step S202 includes one or more of rubber, plastic and fiber. In some embodiments, the polymer matrix is ​​selected from polyacrylonitrile and / or polyvinylidene fluoride.

[0060] According to some embodiments, the polymer matrix is ​​present in the form of one or more of a film, a fiber, a gel, a microsphere, a fabric, and a microcapsule. In some embodiments, the polymer matrix may be present in the form of a film.

[0061] According to an exemplary embodiment, the mass fraction of the polymer matrix relative to the mixed solvent in step S201 is 0.1-2%, preferably 0.5-1.5%, and more preferably 0.8-1.2%. Then, the process proceeds to S203.

[0062] In step S203, the polymer matrix adsorbed with the adsorbate in step S202 is immersed in a poor solvent for deswelling treatment.

[0063] According to an exemplary embodiment, the polymer matrix after swelling and adsorption is immersed in a poor solvent thereof for deswelling treatment, and the good solvent in the polymer matrix diffuses into the poor solvent, thereby removing the good solvent in the polymer matrix to restore the polymer matrix to its original state (i.e., non-swollen state). In some embodiments, the deswelling treatment includes drying the polymer matrix containing the adsorbate, wherein the drying temperature is room temperature to 50° C. and the drying time is 5 to 30 minutes.

[0064] The present invention is described below by means of specific embodiments.

[0065] It should be noted that the reagents used in the embodiments of the present invention are all conventional products that can be purchased commercially, and the reagents are all analytically pure or chemically pure.

[0066] Example 1

[0067] Preparation of PAN (polyacrylonitrile) film: PAN powder (manufacturer: Zhonglian Plastic Chemical Co., Ltd., molecular weight: M W =80000Da) was placed in an oven at 80℃ and dried for 12h. Under 60℃ water bath heating, DMF (N,N-dimethylformamide, N,N-dimethylformamide, manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd. Product purity: analytical grade, DMF used below is the same type) was used as solvent to prepare a PAN casting solution with a solid content of 17%, and it was placed in a vacuum oven for degassing for 12h. Copper wire (diameter 500μm) was wrapped around the glass rod, and the glass rod and the glass plate were placed in an oven at 80℃ for heating. After taking it out, the film was scraped while hot to avoid the high-temperature casting solution from solidifying quickly when it was cooled. Then it was placed in a fume hood for about 12h to evaporate DMF. After DMF evaporated, the glass plate was placed in water and peeled off to obtain a PAN film.

[0068] The prepared PAN membrane was used in the adsorption method provided by the present invention: PAN membrane (0.5 g) was placed in a 100 mg / L MB (methylene blue, manufacturer: Tianjin Tianxin Fine Chemical Development Center, product purity: ≥95%) solution, and the solvent was a DMF / water mixed solvent of different volume concentrations (0-50%, 0% is adsorption in pure water, i.e. non-swelling membrane). The swelling temperature was 30-80°C. Then, the adsorption was carried out in an oscillator at a speed of 150 rpm for 80 min (≥ saturated adsorption time).

[0069] Test Example 1

[0070] 1. First, the de-swelled PAN membrane in Example 1 was scanned by SEM. The results are as follows: Figure 3 Take the six samples in Example 1, which are:

[0071] PAN membrane original membrane;

[0072] The swelling temperature of PAN membrane in DMF aqueous solution with a DMF volume concentration of 70% was 50°C;

[0073] The swelling temperature of PAN membrane in DMF aqueous solution with a DMF volume concentration of 50% was 40°C;

[0074] The swelling temperature of PAN membrane in DMF aqueous solution with a DMF volume concentration of 40% was 60°C;

[0075] The swelling temperature of PAN membrane in DMF aqueous solution with a DMF volume concentration of 40% was 70°C;

[0076] The swelling temperature of PAN membrane in DMF aqueous solution with a DMF volume concentration of 10% is 50°C.

[0077] result Figure 3 As shown, the structure of the polymer matrix of the PAN membrane in the swollen state is not destroyed.

[0078] 2. The concentration of MB before and after adsorption on the PAN film in Example 1 was monitored using an ultraviolet spectrophotometer at a wavelength of 664 nm. The model of the ultraviolet spectrophotometer used was TU-1901.

[0079] The adsorption amount formula used is as follows:

[0080]

[0081] Among them, C0 and C t are the MB concentrations at the initial adsorption and saturated adsorption, respectively, V1 is the volume of the solution (L), and m is the mass of the polymer film (g).

[0082] After swelling treatment, the adsorption capacity of PAN for MB can be increased from 0.42 mg / g to 13.44 mg / g, and the higher the concentration of good solvent and the higher the swelling temperature, the more conducive to adsorption.

[0083] 3. Select the sample in Example 1:

[0084] (1) PAN membrane original film;

[0085] (2) PAN membrane swelling in a DMF aqueous solution with a DMF volume concentration of 50% at a temperature of 25°C;

[0086] (3) immersing the swollen and adsorbed polymer matrix into a poor solvent for deswelling treatment, and the good solvent in the polymer matrix diffuses into the poor solvent, thereby removing the good solvent in the polymer matrix, so that the polymer matrix returns to its original state (i.e., non-swollen state);

[0087] The above samples were analyzed by XRD test, and the results are as follows: Figure 4 As shown, the crystallinity of PAN decreases when it swells, indicating that the creeping property of the polymer chain segments and the increase in free volume can provide more adsorption sites.

[0088] Example 2

[0089] Preparation of PVDF (polyvinylidene fluoride) membrane: PVDF (manufacturer: Dongguan Zhanyang Polymer Materials Co., Ltd., molecular weight: 600,000) powder was placed in an oven at 80°C for 12 hours. DMF was used as a solvent to prepare a PVDF casting solution with a solid content of 17%, and it was placed in a vacuum oven for degassing for 12 hours. Copper wire (diameter of 500 μm) was wrapped around a glass rod, and the glass rod and glass plate were placed in an oven at 80°C for heating. After taking it out, the film was scraped while hot to avoid rapid solidification of the high-temperature casting solution when it was cooled. Then it was placed in a fume hood for about 12 hours to allow DMF to evaporate. After DMF evaporated, the glass plate was placed in water and peeled off to obtain a PVDF membrane.

[0090] The prepared PVDF membrane was used in the adsorption method provided by the present invention: the membrane was placed horizontally, and 25 mL of F-127 (amphiphilic polymer, PEO) was introduced into the membrane with the help of a glass fixing ring (with a diameter of 80 mm). 106 -PPO 70 -PEO 106 , Polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer, manufacturer: Sigma-Aldrich (Shanghai) Trading Co., Ltd., molecular weight: M W =12,600 Da) solution (2%, the solvent is water and DMF aqueous solution with a volume concentration of 50%, DMF concentration is volume concentration in the following text) to contact the membrane surface for a given period of time, and adsorption is carried out at room temperature. Then, the excess adsorption liquid is removed, the unadsorbed solution is rinsed with pure water, and finally the membrane is air-dried (the adsorption in pure water is a non-swelling membrane).

[0091] Test Example 2

[0092] 1. First, the de-swelled PVDF membrane in Example 2 was scanned by FIB-SEM. The results are as follows: Figure 5 Take 7 samples in Example 2, which are:

[0093] PVDF membrane original membrane;

[0094] PVDF membrane in poor solvent water at 25°C

[0095] The swelling temperature of PVDF membrane in DMF aqueous solution with a DMF volume concentration of 10% is 25°C;

[0096] The swelling temperature of PVDF membrane in DMF aqueous solution with a DMF volume concentration of 20% is 25°C;

[0097] The swelling temperature of PVDF membrane in DMF aqueous solution with a DMF volume concentration of 30% is 25°C;

[0098] The swelling temperature of PVDF membrane in DMF aqueous solution with a DMF volume concentration of 40% is 25°C;

[0099] The swelling temperature of the PVDF membrane in a DMF aqueous solution with a DMF volume concentration of 50% is 25°C.

[0100] The results are as follows Figure 5 As shown, the PVDF membrane after adsorption under swelling and non-swelling conditions maintained a dense cross-sectional morphology, indicating that the swelling modification method would not destroy the polymer matrix.

[0101] 2. The surface element content of the PVDF membrane after adsorbing F-127 in Example 1 was analyzed by X-ray photoelectron spectrometer. The model of the X-ray photoelectron spectrometer used was K-alpha.

[0102] Test principle: The XPS spectrum of F-127 contains peaks of C and O elements, and the XPS spectrum of the original PVDF membrane contains peaks of C and F elements. Compared with the original PVDF membrane, the membrane after adsorption of F-127 has a new characteristic peak at 532.3eV, which corresponds to the O1s characteristic signal in the F-127 structure on the membrane surface, indicating that the F-127 molecules have been successfully adsorbed on the membrane surface.

[0103] The results show that the O content of the PVDF membrane after adsorption of F-127 under swelling conditions can reach 15.9%, which is about 4 times higher than that of the PVDF membrane surface without swelling treatment.

[0104] 3. Select the sample in Example 2:

[0105] (1) PVDF membrane original membrane;

[0106] (2) PVDF membrane swelling in a DMF aqueous solution with a DMF volume concentration of 50% (50% DMF aqueous solution) at a temperature of 25°C;

[0107] (3) The swollen and adsorbed polymer matrix is ​​immersed in its poor solvent water for deswelling treatment, and the good solvent in the polymer matrix diffuses into the poor solvent, thereby removing the good solvent in the polymer matrix, so that the polymer matrix returns to its original state (i.e., non-swollen state).

[0108] The above samples were analyzed by XRD test, and the results are as follows: Figure 6 As shown, the crystallinity of PVDF decreases when it swells, indicating that the creeping property of the polymer chain segments and the free volume increase, which can provide more adsorption sites.

[0109] 4. The hydrophilicity of the PVDF membrane surface was analyzed by using a contact angle meter after adsorption in Example 1, and the adsorption firmness of the macromolecules on the PVDF membrane was studied.

[0110] The PVDF membrane after adsorption of F-127 was immersed in water for static desorption or oscillation desorption (oscillation desorption at a speed of 150 rpm in an oscillator) for 6 hours and then dried for contact angle measurement.

[0111] Test principle: F-127 is an amphiphilic polymer. When it is adsorbed on the surface of PVDF membrane, a hydrophobic-hydrophobic interaction is established between the hydrophobic part of PPO and the PVDF skeleton. The hydrophobic PPO segments are combined together due to the hydrophobic interaction with the PVDF membrane, while the hydrophilic PEO segments extend to the outside to improve the hydrophilicity of the membrane surface. Therefore, the more hydrophilic the PVDF membrane surface is, the more F-127 is adsorbed.

[0112] The results show that the contact angle of the original PVDF membrane surface is 93°, the contact angle of the membrane surface after adsorbing F-127 under pure water conditions decreased by 34%, and the contact angle of the membrane surface after adsorbing F-127 under 50% DMF aqueous solution swelling conditions decreased by 58%. In the firmness experiment, compared with before desorption, the contact angle of the membrane after desorption increased. The contact angle of the membrane without swelling modification gradually recovered to almost the same size as the original membrane after soaking, indicating that most of the F-127 was washed away, because at this time there was only a weak hydrophobic interaction between the adsorbed F-127 molecules and the PVDF membrane, so it was easily washed away. In the 50% DMF aqueous solution, i.e., the membrane adsorbing F-127 in the swelling state, after desorption, the contact angle was about 65°, which was much lower than the original membrane, indicating that F-127 was still retained on the membrane surface. That is, the macromolecules adsorbed under non-swelling conditions are easy to desorb, and the macromolecules adsorbed under swelling conditions are relatively firmly planted on the polymer surface.

[0113] Example 3

[0114] The original PVDF membrane was obtained by the membrane preparation method similar to that in Example 2.

[0115] Example 3 The PVDF membrane was used in the provided adsorption method: the membrane was placed horizontally, and 25 mL of F-127 solution (2%, the solvent was water and DMF aqueous solution with a volume concentration of 40%) was introduced with the help of a glass fixing ring (with a diameter of 80 mm) to contact the membrane surface for a given period of time, and adsorption was performed at room temperature. Then, the excess adsorption liquid was removed, the unadsorbed solution was rinsed with pure water, and finally the membrane was air-dried (wherein the adsorption in pure water was non-swelling membrane).

[0116] Test Example 3

[0117] Protein adsorption study was conducted on the PVDF membrane adsorbing F-127 in Example 3:

[0118] Using BSA (bovine serum albumin, Bovine albumin, manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., product purity: 96%) as a model protein, the membrane sample was tested for protein adsorption under static conditions. The sample membrane was cut into 2×3 cm 2 The size of the sample was then soaked in PBS buffer for 0.5 h. After being taken out, it was soaked in BSA solution (0.5 g / L, pH = 7.4) and placed in a 25°C constant temperature oscillator for 2 h to achieve adsorption equilibrium. The BSA concentration of the solution before and after adsorption was measured at 280 nm using an ultraviolet spectrophotometer. Three experimental tests were performed and the average value was taken. The protein adsorption amount (Q) was calculated using formula (2) BSA ):

[0119]

[0120] Where C' and C represent the concentrations of BSA solution before and after adsorption, respectively; S is the effective adsorption area of ​​the membrane sample; and V2 is the volume of the protein solution.

[0121] The results show that protein adsorption on the surface can be reduced by increasing the hydrophilicity of the surface. The protein adsorption on the original membrane surface was 8.2 mg / g. The protein adsorption on the membrane surface after adsorption of F-127 under pure water conditions decreased by 17% (6.8 mg / g). The protein adsorption on the membrane surface after adsorption of F-127 under 40% DMF swelling conditions decreased by 66% (2.8 mg / g). This indicates that more F-127 is adsorbed on the PVDF surface under swelling conditions.

[0122] Example 4

[0123] The original PVDF membrane was obtained by the membrane preparation method similar to that in Example 2.

[0124] Example 4 The PVDF membrane was used in the provided adsorption method: the membrane was placed horizontally, and 25 mL of F-127 solution (2%, the solvent was water and DMF aqueous solution with a volume concentration of 30%) was introduced with the help of a glass fixing ring (with a diameter of 80 mm) to contact the membrane surface for a given period of time, and adsorption was performed at room temperature. Then, the excess adsorption liquid was removed, the unadsorbed solution was rinsed with pure water, and finally the membrane was air-dried (wherein the adsorption in pure water was non-swelling membrane).

[0125] Test Example 4

[0126] Blood compatibility analysis of the PVDF membrane adsorbed with F-127 in Example 4 - platelet and red blood cell adhesion study:

[0127] Cut the PVDF membrane into 1×1 cm 2The size of the membrane was placed in a 24-well culture dish, and PBS buffer was added to each well, and the membrane was balanced at 37°C for 30 minutes. Then the PBS buffer was removed, and 1 mL of platelets or red blood cells were added and incubated at 37°C for 1 hour. After rinsing with PBS three times, the membrane was immersed in a 2.5wt% GA (Glutaraldehyde, Glutaraldehyde, manufacturer: Tianjin Komio Chemical Reagent Co., Ltd., purity: 25%) aqueous solution, and stored at 4°C for 12 hours to fix the platelets and red blood cells on the membrane. After that, glutaraldehyde and unadhered platelets or red blood cells were rinsed with PBS, and the membrane was immersed in ethanol / PBS solutions with a concentration gradient of 25%, 50%, 75%, and 100% for 15 minutes to dehydrate the membrane, and then the alcohol was removed, the membrane was naturally dried, and the membrane was sprayed with gold under vacuum conditions. The adhesion of platelets and red blood cells was observed by SEM.

[0128] Figure 7 This is an electron microscopic image of the adsorption of platelets on the surface of the PVDF membrane in Example Y of the present invention.

[0129] Figure 8 This is an electron microscopic image of the adsorption of red blood cells on the surface of the PVDF membrane in Example Y of the present invention.

[0130] See also Figure 7 and Figure 8 The results showed that a large number of platelets and red blood cells adhered to the surface of the original PVDF membrane. The morphology of some platelets and red blood cells had been deformed and adhered together, proving that they had been activated. The amount of platelet adhesion on the surface of the PVDF membrane after adsorbing F-127 decreased. Under the condition of DMF concentration of 30%, the amount of adhesion on the surface of the PVDF membrane after adsorbing F-127 further decreased, indicating that swelling conditions helped more F-127 to be adsorbed on the surface of the PVDF membrane. Because the hydrophilicity of the surface of the polymer material affects its blood compatibility, poor hydrophilicity can easily cause the adhesion of platelets or red blood cells and the destruction of blood cells.

[0131] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this field, under the technical enlightenment provided by the present invention, as common knowledge in the field, other equivalent variations and improvements can also be made, which should also be regarded as the protection scope of the present invention.

[0132] References

[0133] 【1】Q.Shi,J.Q.Meng,R.S.Xu,X.L.Du,Y.F.Zhang,Synthesis of hydrophilicpolysulfone membranes having antifouling and boron adsorption properties viablending with an amphiphilic graft glycopolymer,Journal of Membrane Science444(2013):50-59.

[0134] 【2】H.S.Sundaram,X.Han,A.K.Nowinski,N.D.Brault,Y.Li,J.R. Ella-Menye,K.A.Amoaka,K.E.Cook,P.Marek,K.Senecal,S.Jiang,Achieving One-step SurfaceCoating of Highly Hydrophilic Poly(Carboxybetaine Methacrylate) Polymers onHydrophobic and Hydrophilic Surfaces,Adv Mater Interfaces 1(6)(2014)。

Claims

1. An adsorption method, characterized in that: The following steps are involved: Step a) selecting a good solvent for the polymer matrix and a poor solvent for the polymer matrix according to the polymer matrix used and preparing a mixed solvent; Step b) placing the polymer matrix and the adsorbate in the mixed solvent formed in step a) to allow the polymer matrix to swell and adsorb the adsorbate; The mass ratio of the good solvent to the poor solvent in step a) is 1:9 to 4:1; The swelling of the polymer matrix in step b) is carried out at a temperature ranging from 25° C. to the glass transition temperature of the polymer matrix; The good solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, n-hexane, water, dichloromethane, n-butanol, dioxane and tetrahydrofuran; The poor solvent includes one or more of ethanol, methanol, propanol, acetone, chloroform, ethyl acetate, hexane, toluene, ether and water; In step b), the polymer matrix comprises one or more of rubber, plastic and fiber; The polymer matrix is ​​present in one or more forms of film, fiber, gel, microsphere, fabric and microcapsule; The mass fraction of the polymer matrix relative to the mixed solvent in step a) is 0.1-2%; The adsorbent in step b) includes macromolecular substances and / or small molecular substances; The macromolecular substance includes one or more of a hydrophilic polymer, a hydrophobic polymer and an amphiphilic polymer; The small molecule substances include one or more of inorganic small molecules, metal ions and organic small molecules.

2. The adsorption method according to claim 1, characterized in that: The good solvent is N,N-dimethylformamide; and / or The poor solvent is water.

3. The adsorption method according to claim 1, characterized in that: In step b), the polymer matrix is ​​polyacrylonitrile or polyvinylidene fluoride; and / or The polymer matrix is ​​in the form of a film; and / or The mass fraction of the polymer matrix relative to the mixed solvent in step a) is 0.5-1.5%.

4. The adsorption method according to claim 3, characterized in that: The mass fraction of the polymer matrix relative to the mixed solvent in step a) is 0.8-1.2%.

5. The adsorption method according to claim 1, characterized in that: The step b) of swelling the polymer matrix is ​​carried out at a temperature of 30-80°C.

6. The adsorption method according to claim 1, characterized in that: The swelling of the polymer matrix in step b) is carried out at a temperature of 40-60°C.

7. The adsorption method according to claim 1, characterized in that: The hydrophilic polymer is one or more of polyvinyl alcohol, chitosan, polydimethylaminoethyl methacrylate, and heparin; and / or The hydrophobic polymer is polydimethylsiloxane or protein; and / or The amphiphilic polymer is one or more of polymethacrylate betaine, polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer and polymethacrylate glycol; and / or The small molecule substance is methylene blue.

8. The adsorption method according to claim 7, characterized in that: The amphiphilic polymer is a polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer.

9. The adsorption method according to any one of claims 1 to 8, characterized in that: The adsorption method further comprises: Step c) immersing the polymer matrix adsorbed with the adsorbate in step b) in a poor solvent for deswelling treatment; The step c) further comprises drying the deswelled polymer matrix, wherein the drying temperature is room temperature to 50° C. and the drying time is 5 to 30 minutes.

10. A composition having a swelling polymer, characterized in that include: polymer matrix; A mixed solvent, comprising a good solvent for the polymer matrix and a poor solvent for the polymer matrix; the mass ratio of the good solvent to the poor solvent is 1:9 to 4:1; The mass fraction of the polymer matrix relative to the mixed solvent is 0.1-2%; The polymer matrix includes one or more of rubber, plastic and fiber; The polymer matrix is ​​present in one or more forms of film, fiber, gel, microsphere, fabric and microcapsule; The good solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, n-hexane, water, dichloromethane, n-butanol, dioxane and tetrahydrofuran; The poor solvent includes one or more of ethanol, methanol, propanol, acetone, chloroform, ethyl acetate, hexane, toluene, ether and water.

11. The composition according to claim 10, characterized in that The mass fraction of the polymer matrix relative to the mixed solvent is 0.5-1.5%.

12. The composition according to claim 10, characterized in that The polymer matrix is ​​polyacrylonitrile or polyvinylidene fluoride; and / or The polymer matrix is ​​in the form of a film; and / or The mass fraction of the polymer matrix relative to the mixed solvent is 0.8-1.2%.

13. The composition according to any one of claims 10 to 12, characterized in that The good solvent is N,N-dimethylformamide; and / or The poor solvent is water.

14. Use of the adsorption method according to any one of claims 1 to 9 or the composition with swelling polymer according to any one of claims 10 to 13 in biology, water treatment, printing and dyeing, and surface modification.

Citation Information

Patent Citations

  • A method for surface modification of polymer films

    CN102274692A

  • Natural porous adsorbing material based on coconut meat as well as preparation method and application thereof

    CN112090405A